Transient Elastography for Assessment of Liver Fibrosis and Steatosis: An Evidence-Based Analysis - Brener, S (Ont Health Technol Assess Ser, 2015)
BACKGROUND: Liver fibrosis is a sign of advanced liver disease and is often an indication for treatment. The current standard for diagnosing liver fibrosis and steatosis is biopsy, but noninvasive alternatives are available; one of the most common is transient elastography (FibroScan). OBJECTIVES: The objective of this analysis was to assess the diagnostic accuracy and clinical utility of transient elastography alone for liver fibrosis and with controlled attenuation parameter (CAP) for steatosis in patients with hepatitis C virus, hepatitis B virus, nonalcoholic fatty liver disease, alcoholic liver disease, or cholestatic diseases. The analysis also aimed to compare the diagnostic accuracy of transient elastography with two alternative noninvasive technologies: FibroTest and acoustic force radiation impulse (ARFI). DATA SOURCES: Ovid MEDLINE, Ovid MEDLINE In-Process, Ovid Embase, and all EBM databases were searched for all studies published prior to October 2, 2014. REVIEW METHODS: An overview of reviews was conducted using a systematic search and assessment approach. The results of the included systematic reviews were summarized, analyzed, and reported for outcomes related to diagnostic accuracy and clinical utility as a measure of impact on diagnoses, therapeutic decisions, and patient outcomes. RESULTS: Fourteen systematic reviews were included, summarizing more than 150 studies. The reviews demonstrated that transient elastography (with or without CAP) has good diagnostic accuracy compared to biopsy for the assessment of liver fibrosis and steatosis. Acoustic force radiation impulse and FibroTest were not superior to transient elastography. LIMITATIONS: None of the included systematic reviews reported on the clinical utility of transient elastography. CONCLUSIONS: Transient elastography (with or without CAP) offers a noninvasive alternative to biopsy for the assessment of liver fibrosis and steatosis, given its comparable diagnostic accuracy.